AKSELERASI BELAJAR KITAB KUNING DENGAN MENGGUNAKAN METODE AMTSILATI DI PONDOK PESANTREN HIDAYATUL MUBTADI’IN AMTSILATI - Hendri; Ahmad Jauhar Fuad; Amik Nadziroh (Jurnal Studi Pesantren, 2026)
Study of kitab kuning (classical Islamic texts) is a distinctive characteristic of traditional Islamic boarding schools (pondok pesantren). Mastery of kitab kuning requires a solid understanding of Arabic grammar (nahwu-sharaf), which many students often find difficult both in theory and practice. The Amtsilati method offers a simplified and systematic approach designed to assist beginners in understanding the Qur’an and kitab kuning. Pondok Pesantren Hidayatul Mubtadi’in Amtsilati Gurah Kediri is among the few pesantren that implement the Amtsilati method in their learning curriculum, whereas most traditional pesantren rarely adopt this method. This study aims to explore the accelerated method of learning kitab kuning using the Amtsilati approach at this pesantren. Employing a qualitative descriptive method, data were collected through field observations, interviews, and documentation. The findings reveal that (1) there are two main systems used in teaching kitab kuning with the Amtsilati method: the regular system and the accelerated (intensive) system. The instructional process emphasizes a structured learning system, modeling approach, repetition, and positive reinforcement through rewards; (2) the impact of this method includes accelerated Arabic comprehension, increased self-confidence, higher motivation and enthusiasm, strengthened practical skills, enhanced responsibility, and reliance on a supportive system.